Positive experience, self‐efficacy, and action control predict physical activity changes: A moderated mediation analysis. (27th September 2012) - Parschau, Linda; Fleig, Lena; Koring, Milena; Lange, Daniela; Knoll, Nina; Schwarzer, Ralf; Lippke, Sonia
<x xml:space="preserve">Abstract</x> Objectives Experiencing positive consequences of one's physical activity is supposed to facilitate further activity. This motivational outcome might be generated by an increase in perceived self‐efficacy. In addition to such a mediator effect, we examine whether this applies generally or only under conditions of volitional control. For this purpose, perceived action control was considered as a putative moderator. Design and Method N = 193 students participated in a study with three measurement points in time. At baseline, positive experience with previous physical activity was measured as a predictor of physical activity. Two weeks later, self‐efficacy and action control variables were assessed as putative mediator and moderator, respectively. After another 2 weeks, physical activity was measured as the outcome. A moderated mediation model was specified with baseline physical activity and sex as covariates. Results Self‐efficacy was found to mediate between initial positive experience and later physical activity, and this mediation was moderated by action control. Conclusions Participants' perceptions of positive experience were associated with their subsequent self‐efficacy fostering physical activity. However, persons with low levels of action control did not translate positive experience into physical activity via self‐efficacy. Statement of contribution What is already known on this subject? Numerous studies have shown that exercise‐specific self‐efficacy predicts subsequent physical activity. Prior positive experience with physical activity is suggested to be associated with exercise‐specific self‐efficacy. Furthermore, action control was found to be beneficial for the maintenance of physical activity. What does this study add? This study unveils the mechanisms between these social‐cognitive determinants: our longitudinal results suggest that the mediation of positive experience and subsequent physical activity via self‐efficacy is moderated by action control. Persons with low levels of action control did not translate positive experience into physical activity via self‐efficacy.